Reflexões sobre a construção histórica do conceito de espaço: uma aproximação - Ramos, Fernando Guillermo Vazquez; Ribeiro, Carlos Eduardo Dias; Campoy, Carlos Quedas; Paula, Franklin Roberto Ferreira de (Risco - Journal of Architecture and Urbanism, 2023)
Nowadays, we are familiar and close to the term space in architecture, but this was not always the case. This paper investigates the position of some authors who began to think about the relationship between space and architecture between the late nineteenth and early twentieth centuries, pointing out the repeated lack of interest in the subject in the 1930-40s, and then facing the approximation concept that took place in the field of architecture in the 1950s-60s. This method of chronological succession allowed us to understand the complexity of the theme and outline a contemporary approach to its understanding, but without concluding with a precise definition, because, after thinking about possible theoretical approaches, it seems unlikely that there is a single meaning for this concept.